SOFT SKILL DAN CHARACTER BUILDING MAHASISWA - -, H a r y u (State Islamic Institute of Madura, 2009)
There are three aspects concerning the development of students, they are cognitive, affective, and psychomotoric aspects. Soft skill is unseperated aspect of affective one. In building students’ character, effective aspect so called soft skill aspect becomes important, moreover, it dominantly determines the succeess. Soft skill is tightly related to the emotional quotient matters. It deals with ones’ ability to motivate themselves, to survive from frustration, to control the will but not to exaggerate the happiness, to control the mood and to manage the stress.